PTU-144 Small-bowel capsule endoscopy for iron deficiency anaemia alone; experience from a tertiary centre. (28th May 2012) - Yung, D E; Lam, J H; Douglas, S; Koulaouzidis, A; Plevris, J N
Abstract : Introduction: Small-Bowel Capsule Endoscopy (SBCE) is a useful diagnostic modality in the investigation of Obscure Gastrointestinal Bleeding (OGIB). Its role though in Iron Deficiency Anaemia (IDA) is less clear. Aim: To assess the usefulness of SBCE in the diagnostic work-up of patients with IDA with neither complicating pathology nor specific GI symptomatology. Methods: Design: Retrospective study. Setting: University hospital & tertiary referral centre for capsule endoscopy for South East of Scotland. A review of SBCE database was carried out for the period between March 2005 and June 2011. Only patients with IDA and no other GI symptoms or known previous diagnosis contributing to IDA for example, Crohn's or coeliac disease were included in the analysis. Electronic and paper case notes were reviewed for information relating to procedure indications, investigations carried out prior to SBCE and subsequent findings. Cases with failed examinations due to SBCE retention and/or incomplete small-bowel transit were excluded from further analysis. SBCE findings were classified as clinically significant (small-bowel malignancy, significant inflammation and/or strictures and coeliac disease) or clinically relevant pathology that is, angioectasias (P1/P2 lesions). Results: A total of 811 SBCE examinations were performed during the above period. IDA as the sole indication for SBCE was recorded in 27% ( n =221; 151F/70M, mean age: 62 yr) patients. All patients had bi-directional endoscopies prior to SBCE. The overall diagnostic yield (DY) of SBCE was 30.7% (68/221). The DY for significant pathology and angioectasias was 9% and 21.7%, respectively. In those ≤40 yr ( n =20; 13F/7M, mean age: 26.5 yr), significant pathology was found in 25% (5/20); in the >40 yr group ( n =201; 138F/63M, mean age: 72.2 yr), significant pathology was found in 7.5% (15/201), p=0.0231. Although none of the patients ≤40 yr had angioectasias, P1 or P2 lesions were found in 48/201 (21.7%) of those >40 yr, p=0.009. Age-range analysis showed angioectasias in 11.1%, 13%, 20% and 42% in the age-groups 41–50, 50–60, 60–70, 70–80 yr, respectively. Interestingly, in those >80 yr ( n =16; 12F/4M, mean age: 82.5 yr) angioectasias were present in 50% of SBCE but no significant pathology was identified. Conclusion: IDA alone is one of the main indications (27%) for referral to the SBCE service of our centre with the majority of referrals coming from the >40 age group. In our cohort, the overall DY of SBCE for IDA is 30.7% and the commonest finding small-bowel angioectasias. The detection rate of significant small-bowel pathology for those >40 yr is low decreasing to zero in the >80 age group. In contrast, 25% of patients ≤40 yr had a significant or sinister diagnosis made with SBCE. Competing interests: None declared.